Knowledge Management in Knowledge Society - Ivan Strugar; Davor Fakleš (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
In spite the fact that individuals or even some companies neglect knowledge as one of key resources of contemporary business, knowledge occupies very important position within these successful companies. Dominant opinion of these individuals is that knowledge can't be measured, and according to that it is not possible to govern with knowledge. Different researches how to implement knowledge and how to maintain required level of knowledge among the company employees proves that this is wrong assumption. Investment in the people, in creation of new knowledge and employee intellectual capital management makes a weapon of new economy in which knowledge is main product and that what is buying and selling. In this globalized market with fierce competition, demand and knowledge creation is key factor. The goal of this paper is to present overview of knowledge management in knowledge society, with point to new trends and challenges.
Keywords: D83; 330; knowledge; knowledge economy; collaboration